Combating Combination of Hypertension and Diabetes in Different Rat Models - Talma Rosenthal; Firas Younis; Ariela Alter (MDPI AG, 2010)
Rat experimental models are used extensively for studying physiological mechanisms and treatments of hypertension and diabetes co-existence. Each one of these conditions is a major risk factor for cardiovascular disease (CVD), and the combination of the two conditions is a potent enhancer of CVD. Five major animal models that advanced our understanding of the mechanisms and therapeutic approaches in humans are discussed in this review: Zucker, Goto-Kakizaki, SHROB, SHR/NDmcr-cp and Cohen Rosenthal diabetic hypertensive (CRDH) rats. The use of various drugs, such as angiotensin-converting enzyme (ACE) inhibitors (ACEIs), various angiotensin receptor blockers (ARBs), and calcium channel blockers (CCBs), to combat the effects of concomitant pathologies on the combination of diabetes and hypertension, as well as the non-pharmacological approach are reviewed in detail for each rat model. Results from experiments on these models indicate that classical factors contributing to the pathology of hypertension and diabetes combination-Including hypertension, hyperglycemia, hyperinsulinemia and hyperlipidemia-can now be treated, although these treatments do not completely prevent renal complications. Animal studies have focused on several mechanisms involved in hypertension/diabetes that remain to be translated into clinical medicine, including hypoxia, oxidative stress, and advanced glycation. Several target molecules have been identified that need to be incorporated into a treatment modality. The challenge continues to be the identification and interpretation of the clinical evidence from the animal models and their application to human treatment.